2006
DOI: 10.1111/j.1460-9568.2006.04904.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood–CSF barrier function in the rat embryo

Abstract: Blood-cerebrospinal fluid (CSF) barrier function and expansion of the ventricular system were investigated in embryonic rats (E12-18). Permeability markers (sucrose and inulin) were injected intraperitoneally and concentrations measured in plasma and CSF at two sites (lateral and 4th ventricles) after 1 h. Total protein concentrations were also measured. CSF/plasma concentration ratios for endogenous protein were stable at approximately 20% at E14-18 and subsequently declined. In contrast, ratios for sucrose (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
101
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(108 citation statements)
references
References 46 publications
7
101
0
Order By: Relevance
“…The presence of AQP1 at E15 strongly suggests CSF formation at this age. This is further supported by the observed expansion of the lateral ventricles immediately after the choroid plexuses first appear [12]. This occurs at a time in development when the pores in roof of the fourth ventricle have not yet formed [15] and the water added to the ventricular space at this time cannot escape and thus contributes to the pressure required for ventricular expansion and proper brain development [7].…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…The presence of AQP1 at E15 strongly suggests CSF formation at this age. This is further supported by the observed expansion of the lateral ventricles immediately after the choroid plexuses first appear [12]. This occurs at a time in development when the pores in roof of the fourth ventricle have not yet formed [15] and the water added to the ventricular space at this time cannot escape and thus contributes to the pressure required for ventricular expansion and proper brain development [7].…”
mentioning
confidence: 76%
“…We have previously suggested that the high CSF protein concentration and specific protein transfer present early in choroid plexus development may be involved in driving CSF formation and ventricular expansion [12,14]. The aim of the present study was to investigate the ontogeny of NKA and CAII in the lateral ventricular choroid plexus in the rat in order to determine if these enzymes also play a role in CSF secretion during early brain development.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Samples of CSF were collected from the fourth ventricle using microcapillary samplers (E12-14, typically 0.5-2 μl) (see Johansson et al, 2006). All CSF samples were microscopically examined for traces of blood over a white background and samples that showed any sign of blood contamination were discarded.…”
Section: Csf Sampling and Analysismentioning
confidence: 99%
“…The ChPs are formed between embryonic day (E) 11 and 14 in the mouse, with the fourth ventricular (hindbrain) ChP differentiating first followed by the two lateral ventricular and later the third ventricular ChP (Dziegielewska et al, 2001). The ChPs acquire barrier, secretory and transport capacities shortly after formation (Møllgård et al, 1976;Ek et al, 2003;Johansson et al, 2005;Johansson et al, 2006;Liddelow et al, 2009;Ek et al, 2010). This early functionality and their localization inside the cerebral ventricles, together with their appearance during the period of neurogenesis, make them uniquely suited for influencing CSF composition and thereby regulating development of the neural stem cells that are in contact with the ventricle along the entire neuraxis (e.g.…”
Section: Introductionmentioning
confidence: 99%